ENGLISH PHONETICS AND ENGLISH TEACHERS - M Fachrudin (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2010)
Fahrudin MA Assulaimaniyah Mojoagung diglossiafbs@gmail.com Abstract In the teaching and learning of English, English phonetics, as a part of linguistics, seems to be neglected. When students want to learn English, they will have to learn to pronounce it. They also have to try to speak in the way the English native speakers. This can be achieved by closely imitating and mimicking them untirelesly until their pronunciation is satisfactory and acceptable. Because of the fact that they could hardly find the native speakers, they tend to imitate their teachers’ pronunciations. Different elements found between their language and the target language is believed to be the causes of the difficulties in pronunciation. Therefore, understanding and applying English phonetics in the teaching and learning of English for English teachers are absolutely important. key words: phonetics, English teachers Abstrak Dalam pengajaran dan pembelajaran bahasa Inggris, Inggris fonetik, sebagai bagian dari linguistik, tampaknya telah diabaikan. Ketika siswa ingin belajar bahasa Inggris, mereka harus belajar untuk melafalkannya. Mereka tentu juga harus mencoba untuk berbicara seperti halnya penutur asli bahasa Inggris. Hal ini dapat dicapai dengan meniru dan meniru sampai pengucapan mereka memuaskan dan dapat diterima. Pada kenyataannya, mereka hampir tidak bisa menemukan penutur asli, mereka cenderung meniru pengucapan guru mereka. Elemen yang berbeda ditemukan antara bahasa mereka dan bahasa target diyakini menjadi penyebab kesulitan dalam pengucapan. Oleh karena itu, memahami dan menerapkan fonetik bahasa Inggris dalam pengajaran dan pembelajaran bahasa Inggris untuk guru bahasa Inggris adalah benar-benar penting dan sangat diperlukan. kata kunci: fonetik, guru bahasa Inggris